2022
DOI: 10.3390/ijms23147732
|View full text |Cite
|
Sign up to set email alerts
|

Function and Application of Flavonoids in the Breast Cancer

Abstract: Breast cancer is one of the top causes of death, particularly among women, and it affects many women. Cancer can also be caused by various factors, including acquiring genetic alteration. Doctors use radiation to detect and treat breast cancer. As a result, breast cancer becomes radiation-resistant, necessitating a new strategy for its treatment. The approach discovered by the researchers is a flavonoid, which is being researched to see if it might help treat radiation-resistant breast cancer more safely than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 112 publications
0
8
0
1
Order By: Relevance
“…Root ethanolic extract's cytotoxic ability is caused by the content of existing metabolites such as flavonoids, tannins, saponins, and terpenoids. Several studies have shown that flavonoids can be developed as chemotherapy agents against breast cancer because they can treat cancer cells by targeting their anticancer effects, such as inhibiting cell growth, protein kinase activity, and inducing apoptosis (Park, et al, 2022;Magne Nde, et al, 2015;Şöhretoğlu, et al, 2021). Many natural terpenoid compounds have been shown to significantly inhibit proliferation, migration, apoptotic resistance, tumor angiogenesis or metastasis in different breast cancer cells/tumors in vitro and in vivo (Ateba, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Root ethanolic extract's cytotoxic ability is caused by the content of existing metabolites such as flavonoids, tannins, saponins, and terpenoids. Several studies have shown that flavonoids can be developed as chemotherapy agents against breast cancer because they can treat cancer cells by targeting their anticancer effects, such as inhibiting cell growth, protein kinase activity, and inducing apoptosis (Park, et al, 2022;Magne Nde, et al, 2015;Şöhretoğlu, et al, 2021). Many natural terpenoid compounds have been shown to significantly inhibit proliferation, migration, apoptotic resistance, tumor angiogenesis or metastasis in different breast cancer cells/tumors in vitro and in vivo (Ateba, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Flavonoid mampu menurunkan proliferasi sel serta meningkatkan aktivitas apoptosis sel kanker payudara. 24 Vitexin merupakan penanda pada tanaman F.deltoidea yang menunjukkan efek sitotoksik pada sel kanker payudara, ovarium dan prostat dengan mekanisme menginduksi apoptosis. 25 Vitexin dapat menurunkan ekspresi beclin-1 atau protein autofag (ATG)5 pada sel HCT-116DR.…”
Section: Efek Anti Kanker Ficus Deltoideaunclassified
“…They trigger programmed cell death within cancer cells, leading to their elimination. Notably, their ability to trigger apoptosis through both intrinsic and extrinsic pathways underscores their significant therapeutic potential (Park et al, 2022).…”
Section: Inducing Apoptosismentioning
confidence: 99%